2012
DOI: 10.1016/j.jconrel.2012.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Size-controlled, dual-ligand modified liposomes that target the tumor vasculature show promise for use in drug-resistant cancer therapy

Abstract: Anti-angiogenic therapy is a potential chemotherapeutic strategy for the treatment of drug resistant cancers. However, a method for delivering such drugs to tumor endothelial cells remains to be a major impediment to the success of anti-angiogenesis therapy. We designed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 28 publications
1
73
0
Order By: Relevance
“…In the present study, it had been demonstrated that lipid composition also affected the uptake efficiency of NGR-SL-C, the cytotoxicity of NGR-SL-B and the targeted delivery of NGR-SL-DiR. In the previous study (Takara et al, 2012), EPC and HSPC were applied for the preparation of rhodamine-labeled NGR-modified and NGR-modified doxorubicin (DOX), respectively. The behavior of these two liposomes was both used to prove the potential of the active targeted liposomes.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In the present study, it had been demonstrated that lipid composition also affected the uptake efficiency of NGR-SL-C, the cytotoxicity of NGR-SL-B and the targeted delivery of NGR-SL-DiR. In the previous study (Takara et al, 2012), EPC and HSPC were applied for the preparation of rhodamine-labeled NGR-modified and NGR-modified doxorubicin (DOX), respectively. The behavior of these two liposomes was both used to prove the potential of the active targeted liposomes.…”
Section: Discussionmentioning
confidence: 79%
“…Consequently, PCs with different T m s were used to prepare NGR-modified liposomes, such as 1,2-dipalmitoyl-sn-glycero-3-phosphatidylcholine (DPPC) (Negussie et al, 2010;Dunne et al, 2011), hydrogenated soy posphatidylcholine (HSPC) (Pastorino et al, 2003;Garde et al, 2007;Takara et al, 2012) or soy posphatidylcholine (SPC) (Luo et al, 2013). The T m s of HSPC and DPPC are determined to be at 53 and 41 C, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…88) NGR motif peptides have been successfully used to deliver drugs as well as liposomes to tumor vasculature. [89][90][91][92] oku and colleagues determined that the alanineplorine-arginine-plorine-glycine (APRPG) motif peptide specifically binds to tumor angiogenic vessels and demonstrated the utility of APRPG-modified PEG liposomes. 93,94) 3.2.…”
Section: -28)mentioning
confidence: 99%
“…The R8 functions as both a cellular uptake device via macropinocytosis and as a mitochondrial targeting peptide via electrostatic interactions with negatively charged mitochondria [17][18][19] . We also developed a dual-ligand system in which the nanocarrier is modified with a specific ligand and R8 20,21 . These systems have a synergistic effect on both selectivity and cellular uptake.…”
Section: Introductionmentioning
confidence: 99%